2016
DOI: 10.1113/ep085771
|View full text |Cite
|
Sign up to set email alerts
|

A 10 km time trial running bout acutely increases the number of angiogenic T cells in the peripheral blood compartment of healthy males

Abstract: What is the central question of the study? Are CD31 angiogenic T (T ) cells preferentially mobilized in response to acute exercise? What is the main finding and its importance? Our study reveals that T cells are redistributed into the circulation in response to acute strenuous exercise, but to a lesser extent than CD31 T cells. Of the T cells mobilized, T cells expressing CXCR4 show greater redistribution compared with CXCR4 T cells. Stromal-derived factor 1-α does not appear to play a role in the redistributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…A single bout of exercise is known to stimulates the movement of EPCs into the peripheral blood compartment in the postexercise period (van Craenenbroeck et al 2008;Ross et al 2014Ross et al , 2018, which may offer a vasculogenic window of adaptation. Previous studies have also observed redistribution of T ANG cells into the circulation with a single bout of exercise, in both young and older men (Ross et al 2016(Ross et al , 2018. This T-cell response is not uncommon, as many T-cell subsets increase in circulation in response to acute exercise stimuli, such as naive T cells (T NA € IVE ), cytotoxic T cells (T CYTOTOXIC ), and regulatory T cells (T REG ) (Brown et al 2014;Spielmann et al 2014;Ingram et al 2015;Clifford et al 2017).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…A single bout of exercise is known to stimulates the movement of EPCs into the peripheral blood compartment in the postexercise period (van Craenenbroeck et al 2008;Ross et al 2014Ross et al , 2018, which may offer a vasculogenic window of adaptation. Previous studies have also observed redistribution of T ANG cells into the circulation with a single bout of exercise, in both young and older men (Ross et al 2016(Ross et al , 2018. This T-cell response is not uncommon, as many T-cell subsets increase in circulation in response to acute exercise stimuli, such as naive T cells (T NA € IVE ), cytotoxic T cells (T CYTOTOXIC ), and regulatory T cells (T REG ) (Brown et al 2014;Spielmann et al 2014;Ingram et al 2015;Clifford et al 2017).…”
Section: Introductionmentioning
confidence: 77%
“…Previous studies have also observed redistribution of T ANG cells into the circulation with a single bout of exercise, in both young and older men (Ross et al. , ). This T‐cell response is not uncommon, as many T‐cell subsets increase in circulation in response to acute exercise stimuli, such as naive T cells (T NAÏVE ), cytotoxic T cells (T CYTOTOXIC ), and regulatory T cells (T REG ) (Brown et al.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations